2018
DOI: 10.1177/2151459318770882
|View full text |Cite
|
Sign up to set email alerts
|

Age and Other Risk Factors Influencing Long-Term Mortality in Patients With Traumatic Cervical Spine Fracture

Abstract: Objective:To identify clinical or demographic variables that influence long-term mortality, as well as in-hospital mortality, with a particular focus on the effects of age.Summary and Background Data:Cervical spine fractures with or without spinal cord injury (SCI) disproportionately impact the elderly who constitute an increasing percentage of the US population.Methods:We analyzed data collected for 10 years at a state-designated level I trauma center to identify variables that influenced in-hospital and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Among the elderly, cervical spine fractures are common, especially compared with other age brackets. 1,2 Of all cervical spine fractures, C2 level fractures have been shown to be most common and have demonstrated an increasing incidence over recent years. 1,3,4 One recent study demonstrated a 135% increase in the rate of C2 fractures from 2000 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Among the elderly, cervical spine fractures are common, especially compared with other age brackets. 1,2 Of all cervical spine fractures, C2 level fractures have been shown to be most common and have demonstrated an increasing incidence over recent years. 1,3,4 One recent study demonstrated a 135% increase in the rate of C2 fractures from 2000 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, <50% of patients required mechanical ventilation at the time of admission and they ascribed higher extubation rate to a Glasgow Coma Scale of 15 and administration of comprehensive multidisciplinary care. In a retrospective analysis of SCI patients admitted to a state-designated Level 1 trauma center in a HIC, Mathew et al reported a hospital stay of 14.1 days and ventilator dependence of 3.5 days, with acute in-hospital mortality of <10% [ 16 ]. Most of the data regarding stay are reported from rehabilitation centers.…”
Section: Discussionmentioning
confidence: 99%
“…Management of cervical spine injury in the elderly remains controversial because of many influencing factors such as the quality of the bone, osteoarthritis, classification, and type of the fracture [6,7,10,19,20]. Treatment might be complicated by numerous comorbidities and reduced bone quality.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the upper cervical spine represent a serious entity including a wide spectrum of pathology ranging from benign to life threatening [1]. Especially in the elderly, these injuries are not uncommon and their incidence will continue to grow due to increasing life expectancy and higher activity levels of the elderly population [5][6][7][8][9]. Currently, the emphasis centers on surgical treatment to obtain good alignment and stability to allow early mobilization.…”
Section: Introductionmentioning
confidence: 99%